Importancia de la formación axiológica en al proceso de enseñanza aprendizaje de la escuela Galo Plaza Lasso del barrio Laipo Grande, parroquia, Juan Montalvo del cantón Latacunga. - Lasluisa Chachapoya, Rita Susana (2020)
Regular education and exclusively education in values are fundamental and essential for personal growth; it is deliberately speculated that values should be assumed as a responsibility only from school; it is suggested that education professionals transfer the various scientific subjects' knowledge, are already forming values. However, the deep crisis that affects Ecuadorian society and the entire world makes the subject matter through this investigation. This study aimed to design a didactic guide to stimulate the development of values in the teachinglearning process in the children of the "Galo Plaza Lasso" school in the Laipo Grande neighborhood, Juan Montalvo parish. The population that participated directly in the research was 76 children, seven teachers, and 56 parents. The survey and interview techniques were applied, the first aimed at teachers, parents, students, and the second structured educational establishment director. The research was characterized by considering the positivist paradigm's mixed-type approach, relying on this effect on the field and bibliographic-documentary research modality. This study shows that, in the Galo Plaza Lasso Educational Unit, the teachers do not adopt the training in values in the different subjects taught in the classrooms, generating physical friction, psychological aggression, and various inconveniences with the students. It was considered pertinent to present a didactic guide that promotes socio-educational and family coexistence that link the child in an educational context in an integral way